Supply-chain legal pluralism: normativity as constitutive of chain infrastructure in the Moroccan argan oil supply chain. Issue 3 (1st September 2016) - Turner, Bertram
ABSTRACT: This article foregrounds the variety and intertwining of legal components that inform the performance of global supply chains. It sheds light on the complexities of normative entanglements that are only cursorily addressed in conventional analyses of chain normativity, which can be divided into roughly three approaches: the first one addresses "voluntary" or "private" standards that are subsumed under the heading of "corporate social responsibility". Second, there is chain law analysis proper as an emerging field in legal studies. Finally, there is a body of literature addressing the interactions between "public" and "private" regulation. In this article, I go beyond these approaches. I argue that, first, other-than-law components of a supply chain, such as technology, also exercise normative power and increase legal complexity inherent in chains. I suggest that the concept of infrastructure as developed in science and technology studies helps us to analyse the interaction of legal and non-legal chain components. Second, I demonstrate that all this chain normativity interacts with the plural legal environment in which chain activities are embedded. The specific case study involves the emergence of Moroccan argan oil on the world market and selectively explores steps in the construction of a "global argan value chain".